Case Report: A case study of perianal paget’s disease in a patient receiving adjuvant photodynamic therapy post-surgery - Wang, Dexin; Liang, Lei; Zhang, Jingyi; Zhang, Xiaohe; Zhang, Xiubi; Tian, Gang; Du, Weiliang; Yue, Chaochi (Frontiers in Surgery, 2025)
BackgroundExtramammary Paget's disease (EMPD) is a rare malignant skin cancer, particularly uncommon in the vulvar and perianal regions, with Perianal Paget's disease (PPD) being an even rarer subtype. Due to its obscure onset location, atypical clinical manifestations, and lack of standardized treatment protocols, PPD poses significant challenges in clinical practice.Case presentationHere, we report a case of a 61-year-old female who presented with a perianal lump discovered a year ago, which had progressively increased in size over the past four months. Imaging and endoscopic examinations revealed no additional tumors elsewhere. The patient underwent Wide local excision surgery with skin flap reconstruction. Histopathological analysis confirmed PPD. After two months from the surgery, the patient received a total of three Photodynamic therapy (PDT). Following treatment, the patient experienced mild pain, which was effectively managed. The flap is currently functioning well, with regular patient monitoring showing no signs of recurrence or metastasis.ConclusionPDT exhibits bactericidal, anti-inflammatory, circulatory enhancement, and antitumor properties, which play a beneficial role in the treatment of PPD. This can aid in standardizing the subsequent treatment protocols for PPD.